Changes in tropical leafing behaviour with climate change over nine decades: A case study from the Singapore Botanic Gardens - Boon‐Chuan Ho; Edmund J. J. Chia; Kwek Yan Chong; Jolyn S. Y. Tan; Wan Xin Tan; Simin Lai; Thereis Y. S. Choo; Puay Yok Tan; Kenneth B. H. Er (Plants, People, Planet)
Societal Impact Statement Long‐term phenology data is crucial to elucidate the effects of climate change on plants, but such efforts are lacking in the tropics. Historical records at the Singapore Botanic Gardens and ongoing phenological monitoring have allowed us to study leafing behaviour and its association with changing rainfall patterns over nine decades in equatorial Singapore. We found that the leafing behaviour of trees in our tropical site changed between 1927 and 2022. This study was made possible by assiduous past and present record‐keeping, and demonstrates the potential of botanical gardens as sentinels of environmental change, which is especially important in the tropics. Summary Understanding tropical phenology and the potential impacts of a changing climate requires long‐term monitoring but such efforts are rare in the tropics. We took advantage of the availability of historical phenological and weather records at the Singapore Botanic Gardens and ongoing phenological monitoring to ask whether leafing behaviour has changed over an exceptionally long period of about nine decades, and whether these changes are associated with changing rainfall patterns in supposedly aseasonal Singapore. Records of leaf flush intervals from 1927 to 1939 in the Singapore Botanic Gardens were compared against leaf flush intervals calculated from present‐day phenological monitoring conducted since 2016. Daily rainfall was modelled as a predictor of present‐day leaf flushing events using moving‐window analyses. Leaf flush intervals have shortened considerably for most of the species that were monitored in the two periods. Mean daily rainfall over a window of 1 to 4 months before was negatively associated with probability of leaf flushing for five species and positively associated with four out of a total of 23 species analysed. Long‐term rainfall records from 1929 to 2022 show that February has become drier and May has become wetter since the 1960s. The results consistently support that more distinctive dry and wet periods today compared to nine decades ago have resulted in more frequent leaf flushing, which may have implications for plant‐herbivore interactions, nutrient cycling and consequently plant health and ecosystem resilience. We also demonstrate the potential and importance of supporting long‐term research in botanical gardens in the tropics.